What native speaker judgments tell us about the grammaticalization of a progressive aspectual marker in Dutch - Flecken, Monique (De Gruyter, 2011)
Abstract This paper focuses on native speaker judgments of a construction in Dutch that functions as a progressive aspectual marker (aan het X zijn, referred to as aan het-construction) and represents an event as in progression at the time of speech. The method was chosen in order to investigate how native speakers assess the scope and conditions of use of a construction which is in the process of grammaticalization. It allows for the inclusion of a large group of participants of different age groups and an investigation of potential age-related differences. The study systematically covers a range of temporal variables that were shown to be relevant in elicitation and corpus-based studies on the grammaticalization of progressive aspect constructions. The results provide insights into the selectional preferences and constraints of the aan het-construction in contemporary Dutch, as judged by native speakers, and the extent to which they correlate with production tasks.
Aus: Linguistics, 49 (2 May 2011), Nr. 3. pp. 479-524. ISSN 1613-396X